2009
DOI: 10.2298/bah0904231k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antimicrobial agents on some chemical and microbiological characteristics of vacuum: Packaged ground buffalo meat stored under refregerated condition

Abstract: Abstract:The chemical characteristics and microbiological examination of vacuum packaged ground buffalo meat during cold storage for 24 days were determined in order to evaluate two different antimicrobial agents sodium lactate, sodium chloride and their mixture. The results indicated that the use of sodium lactate with or without sodium chloride delayed the proliferation of aerobic plate count, psychrotrophic count, and lactic acid bacterial count, and extended the shelf life up to more than 24 and 21 days re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Sallam and Samejima (2004) reported the use of sodium chloride in combination with sodium lactate reduced the microbial growth, maintained the chemical quality and extended the shelf life of ground beef during refrigerated storage. Kenawi et al (2009) reported that the use of sodium lactate with or without sodium chloride delayed the proliferation of aerobic bacterial plate count, psychrotrophic bacterial count and lactic acid bacterial count, and extended the shelf life for up to 24 days, compared to 8 days for the control samples.…”
Section: Sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sallam and Samejima (2004) reported the use of sodium chloride in combination with sodium lactate reduced the microbial growth, maintained the chemical quality and extended the shelf life of ground beef during refrigerated storage. Kenawi et al (2009) reported that the use of sodium lactate with or without sodium chloride delayed the proliferation of aerobic bacterial plate count, psychrotrophic bacterial count and lactic acid bacterial count, and extended the shelf life for up to 24 days, compared to 8 days for the control samples.…”
Section: Sugarsmentioning
confidence: 99%
“…Lactates have been permitted as a natural preservative up to 3 and 100 g meat by the USDA-Food Safety and Inspection Service (Kenawi, 2009 Ascorbic acid: Ascorbic acid (vitamin C), sodium ascorbate and D-isoascorbate (erythorbate) have been used as meat preservatives. Their antioxidant properties can oxidize reactive oxygen species producing water.…”
Section: Sulphitesmentioning
confidence: 99%